Chemoresistance and metastasis in colorectal cancer - Wong, Stephen Qi Rong (Nanyang Technological University, 2022)
Despite major advancements in the understanding of tumor biology and the field of cancer therapeutics in the past decade, drug resistance and metastasis still pose a constant problem for cancer patients that calls for urgent attention and research. In the current thesis, we investigated mechanisms in which colorectal cancer gain resistance to commonly used cytotoxic agents oxaliplatin and irinotecan, making them more metastatic after the course of treatment. The first part of my thesis will describe a study where we observed increased PAI-1 expression in HCT116 treated with ten cycles of clinically relevant doses of oxaliplatin, and demonstrated a functional role of the protein in promoting oxaliplatin resistance and spontaneous metastasis in mice. In a second study, we employed the use of clinically relevant PDX models of CRC to validate the role of HMGA2, an oncofetal protein, in causing sensitivity to irinotecan treatment.